Study on degradation characteristics of imazamox by Streptomycetaceae. Issue 6 (8th June 2022) - Ge, Ling; Wang, Xin; Hou, Jia-Wen; Ni, Zi-Jun; Liu, Wen-Rui; Bao, Jia; Wei, Yu-Lian
Abstract: The residues of imazamox (IMX) will cause phytotoxicity to subsequent crops after long-term use, and will also pollute the soil and its surrounding environment. This study isolates and identifies two strains of Streptomycetaceae JX02 and JX06 that can effectively degrade IMX. Use response surface method Box–Behnken design to optimize physicochemical parameters. The optimal degradation conditions of strains JX02 and JX06 are obtained and verified: IMX concentration is 150 mg L −1, the initial dosage is 9.9%, 9.1% (OD600 = 0.1), the temperature is 26.4 and 27.5 °C, and pH value is 7.0 and 7.7, respectively. The degradation rates of 150 mg L −1 IMX detected by HPLC within 4 d were 99 and 94%, respectively. After adding strains JX02 and JX06, the half-life of IMX in the soil is shortened to 11 d and 13 d, indicating that Streptomycetaceae had a positive effect on the remediation of soil. It is expected to provide scientific information for the rational use, environmental safety evaluation of IMX, and provide a basis for future research and development of microbial agents.